SGLT2 inhibitor, a new bullet in heart failure management - Saidi, Zaki; Widito, Sasmojo (Heart Science Journal, 2024)
The global health landscape is confronted with substantial challenges stemming from diabetes mellitus and heart failure (HF). The escalating incidence of diabetes mellitus (DM), in correlation with HF, underscores the imperative necessity for efficacious strategies in the realm of prevention and management. The most recent advancements in therapeutic approaches, specifically Sodium-glucose transporter 2 inhibitors (SGLT2i), present a promising prospect for enhancing outcomes and addressing the existing gaps in HF management. This paper aims to elucidate the significance of SGLT2i in the therapeutic management of both reduced and preserved heart failure, with or without the presence of DM. SGLT2i are new heart failure drugs. In trials, SGLT2i improved diastolic dysfunction, reduced oxidative stress, inflammation, fibrosis, and myofilament rigidity. The first SGLT2 inhibitor studies, EMPA-REG OUTCOME, DECLARE-TIMI 58, and CANVAS, showed that Empagliflozin and Canagliflozin reduced HF mortality and rehospitalization in type 2 diabetes mellitus (T2DM) patients. Dapagliflozin reduces HF hospitalizations without impacting T2DM mortality. Canagliflozin avoided creatinine rises, kidney disease deaths, and cardiovascular deaths in the CREDENCE Study. SGLT2i improve health in heart failure with preserved ejection fraction (HFpEF). SGLT2i improved health status statistically in the PRESERVED-HF and EMPEROR-Preserved investigations. SGLT2i became known as a promising therapeutic choice in the treatment of HF. The substantial evidence from prominent large-scale clinical trials has substantiated the cardiovascular and renal protective effects of SGLT2i. Furthermore, the benefits of these medications are relevant for individuals who have been diagnosed with heart failure with reduced ejection fraction (HFrEF), as well as those who are experiencing heart failure with preserved ejection fraction (HFpEF).